2008
DOI: 10.1038/mt.2008.52
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Dilated Cardiomyopathy Caused by Targeted Repair of Dystrophic Skeletal Muscle

Abstract: Duchenne muscular dystrophy (DMD) is a fatal disease characterized by deterioration of striated muscle, affecting skeletal and cardiac muscles. Recently, several therapeutic approaches have shown promise for repairing dystrophic skeletal muscles. However, these methods often leave the dystrophic heart untreated. Here we show that, in comparison to fully dystrophin-deficient animals, targeted transgenic repair of skeletal muscle, but not cardiac muscle, in otherwise dystrophin-deficient (mdx) mice paradoxically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 29 publications
9
103
1
1
Order By: Relevance
“…The failure to restore dystrophin in cardiac muscle could severely reduce the clinical value of antisense therapy. Of greater concern is that restoration of dystrophin in skeletal muscles but not in cardiac muscle could exacerbate the existing heart dysfunction as a result of increased workload with the improvement of skeletal muscle function (18). Here we show that PPMO as antisense oligonucleotide chemistry can achieve almost full restoration of dystrophin in cardiac and all skeletal muscles.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The failure to restore dystrophin in cardiac muscle could severely reduce the clinical value of antisense therapy. Of greater concern is that restoration of dystrophin in skeletal muscles but not in cardiac muscle could exacerbate the existing heart dysfunction as a result of increased workload with the improvement of skeletal muscle function (18). Here we show that PPMO as antisense oligonucleotide chemistry can achieve almost full restoration of dystrophin in cardiac and all skeletal muscles.…”
Section: Discussionmentioning
confidence: 71%
“…Because DMD patients live longer owing to improved multidisciplinary patient care, rescuing dystrophin expression in cardiac muscle becomes more critical for their longevity and quality of life (16)(17)(18)(19)(20)(21)(22). More importantly, restoration of dystrophin only in skeletal muscles may exacerbate the failure of heart function if dystrophin expression cannot be effectively restored in cardiac muscle (18). It is not understood why AON does not induce dystrophin expression effectively in cardiac muscle, but low delivery efficiency seems to be the most important contributing factor (15).…”
mentioning
confidence: 99%
“…Measurements of real-time in vivo cardiovascular hemodynamics were obtained using conductance micromanometry as previously described (34,35,53,54). Mice were anesthetized and ventilated via a tracheal cannulation and ventilated via a pressure controlled ventilator with 2% isoflurane at a peak inspiratory pressure of 15 cm H2O and a respiratory rate of 60 breaths/min.…”
Section: Methodsmentioning
confidence: 99%
“…The increased exercise in CKO mice compared with mdx mice causes additional workload and stress on the heart, which would escalate the severity of DCM. Indeed, it has been reported that targeted repair in mdx mice using a skeletal muscle-restricted minidystrophin transgene significantly enhanced cardiac injury and DCM (Townsend et al 2008).…”
Section: Dystrophin Is a Key Target Mediating Dot1l Function In The Hmentioning
confidence: 99%